Biochar applied at an appropriate rate can avoid increasing NH3 volatilization dramatically in rice paddy soil. (February 2017) - Feng, Yanfang; Sun, Haijun; Xue, Lihong; Liu, Yang; Gao, Qian; Lu, Kouping; Yang, Linzhang
Abstract: Biochar application can increase carbon sequestration and reduce greenhouse gases emissions in paddy soils. However, its influence on ammonia (NH3 ) volatilization is neglected. This soil column study was conducted using two biochars (wheat straw pyrolyzed at 500 °C and 700 °C) with two application rates (0.5 wt% and 3 wt%) to evaluate their impact on NH3 volatilization from rice paddy. Results showed that biochar application did not change NH3 volatilization fluxes pattern after N fertilization. Four biochar treatments recorded higher NH3 volatilization (20.50–31.88 kg N ha −1 ) compared with the control (18.65 kg N ha −1 ). Especially, two 3 wt% biochar treatments had significantly 40.8–70.9% higher NH3 volatilization than control. After the basal and first supplementary fertilization, the floodwater pH values were 7.61–7.79 and 7.51–7.76 under biochar treatments, higher than control (7.37 and 7.16, respectively). Meanwhile, after three split N fertilizations, the pH of surface soil received biochar increased by 0.19–0.45, 0.19–0.39, and 0.01–0.21 units, in comparison with the control soil. Furthermore, 3 wt% biochar treatments had higher floodwater and surface soil pH values than 0.5 wt% biochar treatments. Higher NH4 + -N and lower NO3 − -N concentrations of surface soil under biochar application were observed compared with control at tillering stage, whereas they were at similar level at jointing stage. The increased NH3 volatilization at 3 wt% biochar treatments is attributed to increased pH of surface floodwater and soil, and reduced nitrification processes induced by biochar application. Biochar should be applied at lower rate to rice paddy soil, considering the NH3 volatilization. Highlights: Biochar amendments influenced the NH3 volatilization in rice paddy soils. The floodwater and surface soil of biochar treatments recorded higher pH value. Lower nitrogen nitrification rate was found in biochar treatments. Biochar should be applied at a lower rate to the rice paddy soil, considering the NH3 volatilization.